Financial Feasibility Analysis of Mojosari Laying Duck Breeding Farm with Intensive Rearing System (Case Study at UD Sinar Harapan at Kedawung Village Blitar Regency East Java) - Isadora Turnip; Budi Rahayu Tanama Putri; I Wayan Sukanata (SEAS (Sustainable Environment Agricultural Science), 2018)
This research aims to determine the management of maintenance, marketing, and analyze the financial feasibility of duck breeding farms with intensive rearing system. This research was conducted from May to June 2017 at UD. Sinar Harapan located at Kedawung Village, Blitar Regency, East Java. The data used were primary and secondary data. The financial feasibility level of this business was determined based on the analysis of investment criteria, Pay Back Period analysis, Break Even Point, and sensitivity analysis. Business duck breeding mojosari of UD. Sinar Harapan was very concerned for several aspects, i.e. the selection of going, ranching, feeding, prevention and treatment of diseases, labor, and marketing. The results of this research showed that this business produced NPV for Rp 9.484.255.062 IRR for 167,07%, Net B/C for 5,53, Pay Back Period for 0,95 year, and Break Even Point happened in 1,49 year. The sensitivity analysis result shows that this effort is sensitive to the change of egg selling price with sensitivity value 37,98% and less sensitive to the increase of feed price with sensitivity value 92,24%. Based on the analysis of investment criteria that have been done can be concluded that duck breeding business mojosari UD. Sinar Harapan is financially feasible.